CONSTRUCTION OF MULTIPLE DECREMENT TABLES USING THE COMMON DISTRIBUTION OF DECREMENTS ASSUMPTION - Febrisutisyanto, Ady
The multiple decrement model is an extension of the standard model in which several decrements act according to their respective times. This model assumes several different types of decrements, with each offset being disjoint and independent. The multiple decrement model can be constructed into a multiple decrement table. This table consists of age, the number of people who live, the number of people who get out of insurance with each reason, the chance of survival, and the chance of getting out of insurance with each reason. From the multiple decrement tables, annuity structures, premiums, and reserves for life insurance products, as well as pension programs can be constructed. The assumption of CDD (Common Distribution of Decrements) is the development of the classical assumption, namely that the uniform distribution and constant force collaborated with the fractional independent assumption. In practice, actuaries rarely perform splitting and merging of multiple decrement tables. This is because the splitting and merging of multiple decrement tables cannot be done directly using the classical assumption approach. So, this research will carry out procedures regarding splitting and merging multiple decrement tables using the CDD assumption. Finally, two propositions are constructed based on the results of the analysis of the CDD assumption. The numerical result shows there are no significant differences between two propositions at large scale, so in practice these results may not have a big impact.